(untitled) (St. Leonards, NSW, Australia, 1997)
Contents: 1. The emergence of subregional economic zones in Asia edward K. Y. Chen & C.H. Kwan, 2. The south China economic zone joseph siu-lun Lee, 3. The northeast Asian economic zone: potential for the latecomer Yukiko Fukagawa
Keywords: Asia,Châu Á; Economic conditions,Điều kiện kinh tế; 1945-,1945-